EXPLORING CROWDSOURCING FRONTIERS: A POWERFUL APPROACH TO PROBLEM-SOLVING AND INNOVATION - Nasution, Muhammad Dharma Tuah Putra; Sari, Pipit Buana; Rossanty, Yossie; Irawan, Irawan; Rizky, Muhammad Chaerul (JABE (Journal of Applied Business and Economic), 2023)
This study conducts a comprehensive literature review to investigate the impactful utilization of crowdsourcing in problem-solving and innovation, particularly within Small and Medium-sized Enterprises (SMEs). The exploration underscores the capacity of crowdsourcing to leverage collective intelligence, nurture novel product concepts, and facilitate open innovation. Employing a systematic methodology for researching existing literature, the study adheres to a systematic approach to amalgamate knowledge, delineate research trends, and pinpoint future avenues in crowdsourcing, explicitly focusing on content analysis and systematic methodologies. She was acknowledged as a potent instrument for innovation and problem-solving; crowdsourcing bears substantial implications for diverse domains, especially within SMEs. Despite the recognized advantages, unexplored facets and potential challenges persist, necessitating thorough research to comprehend the mechanisms for seamlessly integrating crowdsourcing into SME operations. Future studies should give precedence to exploring the roles of leadership, organizational learning, and the impact of crowdsourcing on SME performance to propel advancements in understanding within this context